Early vs. Late Onset Cardiac Injury and Mortality in Hospitalized COVID-19 Patients in Wuhan - Sun, Wei; Zhang, Yanting; Wu, Chun; Wang, Shuyuan; Xie, Yuji; Zhang, Danqing; Yuan, Hongliang; Zhang, Yongxing; Cui, Li; Li, Meng; Zhang, Yiwei; Li, Yuman; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Increasing evidence points to cardiac injury (CI) as a common coronavirus disease 2019 (COVID-19) related complication. The characteristics of early CI (occurred within 72h of admission) and late CI (occurred after 72h of admission) and its association with mortality in COVID-19 patients is unknown. Methods: This retrospective study analyzed patients confirmed with COVID-19 in Union Hospital (Wuhan, China) from Jan 29th to Mar 15th, 2020. Clinical outcomes (discharge, or death) were monitored to April 15, 2020, the latest date of follow-up. Demographic, clinical, laboratory, as well as treatment and prognosis were collected and analyzed in patients with early, late CI and without CI. Results: A total of 196 COVID-19 patients were included for analysis. The median age was 65 years (interquartile range [IQR] 56-73 years), and 112 (57.1%) were male. Of the 196 COVID-19 patients, 49 (25.0%) patients had early and 20 (10.2%) patients had late CI, 56.6% developed Acute-Respiratory-Distress-Syndrome (ARDS) and 43 (21.9%) patients died. Patients with any CI were more likely to have developed ARDS (87.0% versus 40.2%) and had a higher in-hospital mortality than those without (52.2% versus 5.5%, P<0.001). Among CI subtypes, a significantly higher risk of in-hospital death was found in patients with early CI with recurrence (19/49 patients, adjusted odds ratio [OR]=7.184, 95% CI 1.472-35.071) and patients with late CI (adjusted OR=5.019, 95% CI 1.125-22.388) compared to patients with early CI but no recurrence. Conclusions CI can occur early on or late after, the initial 72 hours of admission and is associated with ARDS and an increased risk of in-hospital mortality. Both late CI and recurrent CI after the initial episode were associated with worse outcomes than patients with early CI alone. This study highlights the importance of early examination and periodical monitoring of cardiac biomarkers to identify predictors and markers of clinical deterioration in COVID-19 patients to guide intervention.